HUBUNGAN KEGIATAN LITERASI DASAR DENGAN MINAT BACA SISWA KELAS V SD NEGERI 53 BANDA ACEH - Noni Zahara; Maulidar Maulidar; Indah Suryawati; Rifaatul Mahmuzah; Tri Putri Utami (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
The purpose of this study was to find out how the relationship between basic literacy activities and reading interest of fifth grade students at SD 53 Banda Aceh. It is known that the reading interest of class V students at SD Negeri 53 Banda Aceh is good. These results can be seen from the questionnaires answered by students. The approach used in this study is a quantitative approach to the type of correlation or correlational research, using questionnaire data collection techniques and documentation, for the subject of 20 students of class V SD 53 Banda Aceh. The results of the study by calculating the reading interest questionnaire of fifth grade students at SD Negeri 53 Banda Aceh were classified as high, students could read well and fluently according to their abilities. Meanwhile, based on the results of the research correlation test, it was found that the correlation coefficient (r) related to literacy activities and students' reading interest was 0.50. This shows that between variable X (basic literacy) and variable Y (reading interest) has a moderate and sufficient correlation. Thus it can be seen that there is a correlation between variables X and Y. X (basic literacy) and variable Y (reading interest). The t-count value > t table or 0.79 > 1.72913 then the alternative hypothesis is accepted. Thus the alternative hypothesis is there is a significant correlation between basic literacy and the interest of fifth grade students at SD Negeri 53 Banda Aceh